The significance of DNA repair system in transformation to cancer cells in menopausal women - Romanowicz-Makowska, Hanna; Smolarz, Beata; Makowski, Marcin; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2009)
DNA repair system plays an important role in keeping the integrity of genome which undergoes changes caused by exo- and endogenous factors. Protein products of over 70 genes, involving directly in repair, take part in some repair systems in humans. Repair process usually consists of two steps: excision of DNA damage and repair synthesis. On the contrary, direct repair and recombination repair differ from excision repair systems: base excision repair, nucleotide excision repair and mismatch repair. Direct repair is one-step process which maintains the integrity of DNA phoshodiester bonds. Defects of proteins, which directly participate in the DNA repair and its regulation are linked with cancer predisposition and other diseases like growth retardation, progressive neurological degeneration, mental retardation, immunodeficiency or prematurely aged facies.